Determination of Best Location for Elevated Tank in Branched Network (Journal of Engineering, 2018)
The research focuses on determination of best location of high elevated tank using the required head of pump as a measure for this purpose. Five types of network were used to find the effect of the variation in the discharge and the node elevation on the best location. The most weakness point was determined for each network. Preliminary tank locations were chosen for test along the primary pipe with same interval distance. For each location, the water elevation in tank and pump head was calculated at each hour depending on the pump head that required to achieve the minimum pressure at the most weakness point. Then, the sum of pump heads through the day was determined. The results proved that there is a most economical location where the energy consumption is minimum. This location joined with the branched line that containing the most weakness point. The best location didn’t join with the highest demand location unless this location containing the most weakness point.  The results indicated that the moving of tank away from best location in pump direction result in pump head increasing that exceed the increasing in pump head when the tank moves in the opposite direction. The location of tank beside the pump station was the worst location. Also, the results showed that as the distance between the pump and the highest demand become shorter, the required pump head become less. The uniform demand distribution required the least amount of pump head, it required minimum head of (554)m while the networks, that have highest demand at distance 200m,400m, and 1000m from the pump station,  required minimum head of 651m, 682m, and 726m respectively.